A system dynamics model for energy transition: Substituting fossil fuels with renewable energy - Joko Sulistio; Winda Nur Cahyo; Daffa Alamsyah; Danang Setiawan (OPSI, 2026)
This study develops a system dynamics model to examine Indonesia's transition from conventional energy to renewable energy. The risk of transition planning fails when the reciprocal relationship between market profitability and investor behavior is poorly considered. The model is built on PowersimStudio 10, representing conventional and renewable energy as stocks connected by bidirectional and interacting substitution flows. The probability of substitution is determined by the relative willingness to invest, which is influenced by a leveledenergy and electricity purchase agreement. Although these parameters are hypothetical, they are based on relevant literature and developed in the context of Indonesian energy. The simulation results show that the transition follows three phases: initial acceleration, stabilization, and dynamic equilibrium. Sensitivity analysis showed that the elasticity of substitution alone did not determine the speed of the transition. The rapid shift only occurs when renewables become more economically attractive than conventional energy. High elasticity is not enough when fossil energy remains economically dominant. The model is intended to provide a conceptual framework for understanding how economic competitiveness, policy signals, and investor behavior together shape the dynamics of the energy transition. Its structure can help identify the policy conditions needed to strengthen the adoption of renewable energy.